Ibrutinib-induced cardiomyopathy. Issue 1 (2nd January 2019) - Kyi, Htay Htay; Zayed, Yazan; Al Hadidi, Samer
ABSTRACT: The use of ibrutinib for the treatment of chronic lymphocytic leukemia (CLL) and other hematologic malignancies is blooming. Atrial fibrillation is a known side effect of ibrutinib but cardiomyopathy was not reported previously. We present an 88-year-old man with CLL who was admitted to the hospital with new-onset atrial fibrillation and symptomatic systolic congestive heart failure one month after ibrutinib initiation. Although ibrutinib was discontinued, the patient continues to have a low ejection fraction four months after discontinuation. Ischemic heart disease was ruled out with normal cardiac catheterization. This case highlights a possible new side effect of ibrutinib that needs to be monitored while patients receive this medication.